Factors Related to Premature Sex Among Junior High School Students in Noenmaprang District in Phitsanulok - บัวชื่น, รัชนิฐตา (Disease Control Journal, 2009)
The objectives of this research were to study sexual behavior risks and factors induced to having sex, live skills in protecting having inappropriate sex and to study related factors leading to sexual behavior of junior high school student of Noenmaprang District, Phitsanulok The study was conducted by quantitative survey on 424 junior high school students (Matayom 1-3) in Noen Maprang District, Phitsanulok, the academic year 2007, by using self-administrated questionnaire 95% of confident level. The quantitative data were analyzed by descriptive statistics Chi-square test. The survey results indicated that the risk behaviors exposed to sexual activities among the students were having a lover, alcoholic beverage intake, watching and reading pornography. About 9.7% of the sample reported experiencing sexual activities, 12% from normal high school and 7.2% from extended opportunity high school and male were higher than female. The average age of having first sexual experience was 14. The majority of the students had sex with their lovers. Among those with sexual experience, 18.2% ever had pregnancy of which 28.6% reported having abortion. The majority of students exhibited the cognitive domain of life skills in the level that needed improvement. On the contrary, the affective and psychomotor domains were in high levels. Factors implicitly of relating to premature sexual behavior statistics were caring style in family, general attitude towards sex, attitude toward having lovers, behavior towards lover, passion of sex, curiosity about sex, having premature sexual behavior, feel guilty about sex, contraception and abortion, problem-solving and decision making skills, emotion and stress management skills, general psychomotor skills and other related risk factors.